Evaluation of a 0.75 × 109/L absolute neutrophil count cut‐off for antimicrobial prophylaxis in canine cancer chemotherapy patients. (16th October 2019) - Bisson, Jocelyn L.; Fournier, Quentin; Johnston, Emily; Handel, Ian; Bavcar, Spela
Abstract: Absolute neutrophil count (ANC) cut‐offs for antimicrobial prophylaxis in veterinary cancer chemotherapy patients are empirical and vary between institutions. Evidence based cut‐offs are vital for antimicrobial stewardship, particularly as global antimicrobial resistance rises. The primary objectives of this study were to evaluate the tolerability of a <0.75 × 10 9 /l ANC cut‐off for antimicrobial prophylaxis in dogs after receiving chemotherapy and its impact on antimicrobial prescription. Predicted nadir ANCs (pnANCs) were stratified into six groups (<0.75 × 10 9 /l [receiving antimicrobial prophylaxis], 0.75‐0.99 × 10 9 /l, 1‐1.49 × 10 9 /l, 1.5‐1.99 × 10 9 /l, 2.0‐3.59 × 10 9 /l and 3.6‐12 × 10 9 /l [reference interval]). The incidences of post‐nadir febrile neutropenia (FN) and non‐haematological toxicity (NHT) were compared between groups. Five hundred and eighty‐six pnANCs were recorded for 181 dogs. There were four episodes of post‐nadir FN and 90 episodes of post‐nadir NHT. There was no significant difference in incidence of post‐nadir FN ( P = .063) or post‐nadir NHT ( P = .084) between pnANC groups. Antimicrobial prophylaxis was prescribed following 8.8% of the chemotherapy administrations; had cut‐off values of <1.0 × 10 9 /l or <1.5 × 10 9 /l been used it would have been prescribed in 15.3% and 25.8% of cases respectively. An ANC cut‐off of <0.75 × 10 9 /l for antimicrobial prophylaxis appears to be well tolerated and minimizes the prescription of antimicrobials.